1990
DOI: 10.1007/bf00117563
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory models of major depression and implications for help-seeking among immigrant Chinese-American women

Abstract: This study explores the explanatory models of major depression in a group of 40 recently immigrated Chinese-American women, and demonstrates the significant relationship between problem conceptualization and help-seeking behavior. Respondents are presented a vignette depicting major depression, from which they are asked to conceptualize the problem described and answer questions regarding its cause, impact and potential sources for help-seeking. Those who provide a psychological conceptualization are likely no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 25 publications
3
88
2
Order By: Relevance
“…Physiological causation is positively associated with preferences for medical doctor and TCM physician as sources of help. This pattern is similar for both depressive and anxious symptoms, and duplicates previous findings (Banerjee & Roy, 1998;Lee, 2007;Ying, 1990). As the health beliefs of adolescents in this study are embedded in both biomedical and traditional Chinese medicines, they may be receptive to seeking help from both types of practitioners.…”
Section: Relationships Between Causal Attribution and Preferred Sourcsupporting
confidence: 88%
See 2 more Smart Citations
“…Physiological causation is positively associated with preferences for medical doctor and TCM physician as sources of help. This pattern is similar for both depressive and anxious symptoms, and duplicates previous findings (Banerjee & Roy, 1998;Lee, 2007;Ying, 1990). As the health beliefs of adolescents in this study are embedded in both biomedical and traditional Chinese medicines, they may be receptive to seeking help from both types of practitioners.…”
Section: Relationships Between Causal Attribution and Preferred Sourcsupporting
confidence: 88%
“…This pattern is similar for both depressive and anxious symptoms, and is consistent with previous findings (Boey, 1999;Chen, 1987). However, contrary to the research hypothesis and previous findings (Lee, 2007;Ying, 1990), psychosocial causation is not statistically related to family and friend/classmate as sources of help. This may be due to the items used for measuring the construct of psychosocial causation.…”
Section: Relationships Between Causal Attribution and Preferred Sourccontrasting
confidence: 85%
See 1 more Smart Citation
“…Evidence for this was poignantly illustrated by patients who linked emotional and physical health to a ''stable heart.'' A similar holistic conceptualization of health was reported by new Chinese immigrant women who attributed depression to both psychological and physical factors including ''heart problems'' (Ying, 1990). Such conceptualizations point to the Chinese cultural belief that the heart is the ''ruler'' of a person's thoughts, emotions and intelligence (Tung, 1994).…”
Section: Discussionmentioning
confidence: 84%
“…T ata and Leong (1994) found that cultural values, social support, network orientation and acculturation influenced Chinese American students' attitudes towards seeking professional psychological help. Ying (1990) observed that Chinese-American women's conceptualization of the problem (whether physical or psychological) determined their help-seeking patterns. While the above-mentioned studies are pioneering studies on the help-seeking behaviour of Chinese people and the related determinants, they have two limitations.…”
mentioning
confidence: 97%